Biaxial Flexural Strength and Vickers Hardness of 3D-Printed and Milled 5Y Partially Stabilized Zirconia - Sebastian Hetzler; Carina Hinzen; Stefan Rues; Clemens Schmitt; Peter Rammelsberg; Andreas Zenthöfer (Journal of Functional Biomaterials)
This study compares the mechanical properties of 5-mol% yttria partially stabilized zirconia (5Y-PSZ) materials, designed for 3D printing or milling. Three 5Y-PSZ materials were investigated: printed zirconia (PZ) and two milled zirconia materials, VITA-YZ-XT (MZ-1) and Cercon xt (MZ-2). PZ samples were made from a novel ceramic suspension via digital light processing and divided into three subgroups: PZ-HN-ZD (horizontal nesting, printed with Zipro-D Dental), PZ-VN-Z (vertical nesting, printed with Zipro-D Dental) and PZ-VN-Z (vertical nesting, printed with Zipro Dental). Key outcomes included biaxial flexural strength (ISO 6872) and Vickers hardness (n ≥ 23 samples/subgroup). Microstructure and grain size were analyzed using light and scanning electron microscopy. Printed specimens exhibited biaxial flexural strengths of 1059 ± 178 MPa (PZ-HN-ZD), 797 ± 135 MPa (PZ-VN-ZD), and 793 ± 75 MPa (PZ-VN-Z). Milled samples showed strengths of 745 ± 96 MPa (MZ-1) and 928 ± 87 MPa (MZ-2). Significant differences (α = 0.05) were observed, except between vertically printed groups and MZ-1. Vickers hardness was highest for PZ-VN-Z (HV0.5 = 1590 ± 24), followed by MZ-1 (HV0.5 = 1577 ± 9) and MZ-2 (HV0.5 = 1524 ± 4), with significant differences, except between PZ and MZ-1. PZ samples had the smallest grain size (0.744 ± 0.024 µm) compared to MZ-1 (0.820 ± 0.042 µm) and MZ-2 (1.023 ± 0.081 µm). All materials met ISO 6872 standards for crowns and three-unit prostheses in posterior regions.